2005
DOI: 10.1309/gjwn-pd8h-u5ma-j837
|View full text |Cite
|
Sign up to set email alerts
|

Blastic NK-Cell Lymphomas (Agranular CD4+CD56+ Hematodermic Neoplasms): A Review

Abstract: Blastic natural killer (NK) cell lymphoma (also termed CD4+CD56+ hematodermic neoplasm) is a recently described entity, with the first case reported in 1994. It was suggested initially that the disease originates from NK cells. Since 1994, single cases and a few small series have been published. In this review, data from the literature and a series of 30 cases from the French and Dutch study groups on cutaneous lymphomas are discussed. The major clinical, histopathologic, and phenotypic aspects of the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
256
1
13

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(277 citation statements)
references
References 0 publications
7
256
1
13
Order By: Relevance
“…13,23,24 In our series cytogenetic analysis confirmed that most patients had unfavorable cytogenetics (48%), among which complex karyotype was a distinctive feature. Moreover, as recently found, 25 no patients had NPM1 mutations.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…13,23,24 In our series cytogenetic analysis confirmed that most patients had unfavorable cytogenetics (48%), among which complex karyotype was a distinctive feature. Moreover, as recently found, 25 no patients had NPM1 mutations.…”
Section: Discussionsupporting
confidence: 74%
“…As for the therapy-related forms of BPDCN, all six affected patients received chemotherapy for the first neoplasm; the two patients with prostate cancer also received radiotherapy; the patient with a previous non-Hodgkin's lymphoma 4 years ago underwent a double autologous HSCT. The median time of latency between the first exposure to cytotoxic treatment for the primary neoplasm and the diagnosis of BPDCN was 5 years (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 þ CD56 þ hematodermic neoplasms [1][2][3] have been variably referred to as blastic NK-cell lymphomas, 4,5 CD56 þ blastic tumors, 6 CD4 þ CD56 þ lineage-negative malignancies, 7 blastic type 2 dendritic cell leukemia, 8 and plasmacytoid dendritic cell leukemia/lymphoma. 9 CD4 þ CD56 þ hematodermic neoplasms are characterized by presentation as extranodal masses that are often cutaneous, with eventual leukemic dissemination and a clinically aggressive course.…”
mentioning
confidence: 99%
“…15 For example, variable expression of CD2, CD7, CD33, CD36, and CD68 has been demonstrated and a subset of cases display terminal deoxynucleotidyl transferase (TdT) immunoreactivity. 1,3,[16][17][18] Blood dendritic cell antigen-2 (BDCA-2) is a recently described cell-surface protein that is selectively expressed on plasmacytoid dendritic cells. 19 Primary amino-acid sequence homology suggests that BDCA-2 (CLEC4C, HECL, CD303) may act as a carbohydrate-binding protein of the C-type lectin family, although specific ligands have not been reported.…”
mentioning
confidence: 99%